BASQUE LEGISLATION ON COOPERATIVES IN LIGHT OF THE NEW BASQUE COOPERATIVE LAW - Alkorta, Aitor Bengoetxea; Pérez, Itziar Villafáñez (International Journal of Cooperative Law, 2025)
On 20 December 2019, Law 11/2019 wasapproved,on Basque Cooperatives, the current regulation for these organisations in their applicable territorialfield, in otherwords,the Basque Autonomous Community. The analysis of this law is highly interesting, whether taking account of the importance and referential nature of the Basque cooperativemovement, or of the new features and clarifications introduced by said Law, which may certainly be controversial. This work reviews the legislation applicable to Basque cooperatives, highlighting the new features introduced by thenew law.